Reconstructing the Legal Status of Women's Make-Up in Islamic Family Law: A Maqasid al-Shari'ah Perspective - Khoirunnas Khoirunnas; Debi Fitria Sari; Ahmad Suryadi Ahmad Suryadi (Jurnal Elsyakhshi, 2026)
This study aims to reconstruct the legal understanding of women's make-up within the framework of Islamic Family Law through a maqasid al-shariah perspective in response to the evolving role of cosmetics in the lives of contemporary Muslim women. The research employs a normative legal method using conceptual and maqasid al-shariah approaches. The data consist of primary, secondary, and tertiary legal materials collected through a literature review of the Quran, hadith, classical fiqh literature, statutory regulations, and contemporary scholarly works. The data were analyzed qualitatively using content analysis by comparatively examining the perspectives of classical jurists and contemporary Muslim scholars. The findings reveal that the four major Sunni schools of Islamic jurisprudence share a common recognition of the permissibility of women's adornment while differing in their legal methodologies concerning its purposes, limits, and social implications. Contemporary scholars further reinterpret adornment through a purpose-oriented approach that emphasizes the objectives of Islamic law, family welfare, and human dignity. The analysis also demonstrates that adornment constitutes a reciprocal right and responsibility of both spouses in fostering marital harmony and maintaining mutual respect. Based on these findings, this study reconstructs the legal status of women's make-up through a maqasid al-shariah framework in which legal rulings are determined by intention, context, proportionality, and their contribution to protecting religion, human dignity, family harmony, and public welfare rather than by cosmetic use itself. This study contributes to the development of Islamic Family Law by integrating classical fiqh with contemporary maqasid al-shariah reasoning to formulate a more contextual, teleological, and socially responsive legal framework.